IMPROVING HISTORY LEARNING ACHIEVEMENT THROUGH TEACHING VARIATION AT SENIOR HIGH SCHOOL 2 GORONTALO - Suko, Maimun; Yunus, Resmiyati; Mondong, Tonny Iskandar (CV. Fahr Publishing, 2025)
Teaching variation is one of the important strategies in the learning process, including in history learning. This study aims to describe teaching variations in learning that have been developed by teachers and to see how teachers deal with obstacles and solutions in implementing teaching variations. The research method used is a qualitative method using data sources from interviews, observations, and documentation of this study. The results of the study indicate that the use of teaching variations, such as a combination of lecture methods, discussions, and media utilization, can significantly increase students' interest in learning. It can be concluded that the use of teaching variations can be an effective solution to create more interesting, interactive, and relevant history learning with students' needs. It is hoped that history teachers can continue to develop creativity in implementing variations in learning methods so that students are more enthusiastic in learning history and are able to understand the material more deeply.